2020
DOI: 10.3390/met10121615
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Structure Design: A Strategy for Outstanding Mechanical Properties in Structural Materials

Abstract: Structured heterogeneous materials are ubiquitous in a biological system and are now adopted in structural engineering to achieve tailor-made properties in metallic materials. The present paper is an overview of the unique network type heterogeneous structure called Harmonic Structure (HS) consisting of a continuous three-dimensional network of strong ultrafine-grained (shell) skeleton filled with islands of soft coarse-grained (core) zones. The HS microstructure is realized by the strategic processing method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Figure 6 a shows a schematic of the true stress–true strain curve for homogenous materials [ 9 ]. Generally, metals undergo strain hardening during deformation, which may assist in bearing loads during deformation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 a shows a schematic of the true stress–true strain curve for homogenous materials [ 9 ]. Generally, metals undergo strain hardening during deformation, which may assist in bearing loads during deformation.…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that necking or localized deformation, which is accompanied by a reduction in the cross-sectional area of the tensile specimen, occurs when the increase in stress is higher than the increase in the load-carrying ability of the metal due to strain hardening [ 8 ]. Therefore, as shown in Figure 6 a, the point of necking under tensile stress is obtained at the point where the strain rate hardening equals the stress (dσ/dε σ) in the true stress–true strain curve [ 9 ]. Typically, homogenous materials exhibit high strength but poor ductility owing to their poor strain-hardening capabilities, as indicated in Figure 6 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmonic microstructures lead to a homogeneous distribution of strain, while plastic activity occurs and avert plastic deformation localization due to an accommodation of plastic deformation induced by the strain distribution in the coarse grains domains, which lead to an accommodation of work hardening to large strain values [20,21]. All the studies carried out to date have shown that harmonic structures improved mechanical properties compared to conventional fine-grained or ultra-fine microstructures [20][21][22][23][24][25]. In particular, a much better synergy between mechanical strength and ductility was observed [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…All the studies carried out to date have shown that harmonic structures improved mechanical properties compared to conventional fine-grained or ultra-fine microstructures [20][21][22][23][24][25]. In particular, a much better synergy between mechanical strength and ductility was observed [18,21]. This results from the microstructure's heterogeneous character, which induces the delocalization of the deformation due to the grain size gradient [26], thus delaying the plastic instability during uniaxial tensile tests, for example [17].…”
Section: Introductionmentioning
confidence: 99%